Refractory True Torsade de Pointes after Adalimumab Therapy in a Patient with Crohn’s Disease Successfully Treated by Stellate Ganglion Block: A Case Report - Yadav, Vijay; Gajurel, Ratna Mani; Poudel, Chandra Mani; Thapa, Sanjeev; Manandhar, Bhawani; Pandey, Kundan Raj; Poudel, Dhiraj; Shrestha, Ninadini (Nepalese Heart Journal, 2025)
Several studies have reported the occurrence of new-onset cardiomyopathy and ventricular arrhythmias (VAs) after the administration of Adalimumab. We report the case of a 20-year-old male who presented himself with the features of dilated cardiomyopathy and a left ventricular ejection fraction of 10-15% after two weeks of administration of adalimumab. During the hospital stay, he developed multiple episodes of VAs (true torsade de pointes) in the form of electrical storm, which were refractory to both pharmacological and electrical interventions. He eventually underwent ultrasonographic guided left-sided stellate ganglion block with 6 mL of 0.2% bupivacaine and 40 mg of methylprednisolone injection. There was no recurrence of ventricular arrhythmias for 72 hours after the procedure.